2005
DOI: 10.1021/la050594p
|View full text |Cite
|
Sign up to set email alerts
|

A Green Chemical Approach to the Synthesis of Tellurium Nanowires

Abstract: Starch, an economical and safe carbohydrate, has been found to be not only an effective reducing agent but also a new morphology-directing agent for the synthesis of tellurium nanowires using commercial H2TeO4 precursor. The obtained tellurium nanowires are of single-crystal in nature, with an average diameter of approximately 25 nm and length up to 10 microm. A possible synthetic mechanism involves the chain-shaped bioorganic molecule acting as a template for the one-dimensional growth of inorganic tellurium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…Tellurium nanoparticles are attracting considerable interest because of their semiconductor and fluorescence properties (CdTe quantum dots) (7,9,12,21,28). "Green" chemical principles have been developed for the synthetic manufacture of these materials (38), and an important consideration for green technologies is the generation of toxic side products of synthetic reactions, like the DMTe, DMDTe, and DMTeS species documented here. While not measured, it is likely that B. selenitireducens and S. barnesii also produce these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Tellurium nanoparticles are attracting considerable interest because of their semiconductor and fluorescence properties (CdTe quantum dots) (7,9,12,21,28). "Green" chemical principles have been developed for the synthetic manufacture of these materials (38), and an important consideration for green technologies is the generation of toxic side products of synthetic reactions, like the DMTe, DMDTe, and DMTeS species documented here. While not measured, it is likely that B. selenitireducens and S. barnesii also produce these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum oxide nanoparticles were obtained by a green approach using sucrose as a reducing as well as stabilizing agent [17][18][19]. The nanoparticles exhibited interesting morphology when synthesized under hydrothermal conditions in the matrix of sucrose-rich medium.…”
Section: Resultsmentioning
confidence: 99%
“…Tellurium nanowires have been synthesized previously, using hydrazine as a reducing agent and a combination of surfactants that rely on or produce harmful reagents and by-products (Mayers & Xia 2002;Mo et al 2002). It was found that, by using starch as a reducing sugar, the compound H 2 TeO 4 $2H 2 O could be reduced under hydrothermal conditions to form tellurium nanowires in a high yield (Lu et al 2005). As well as being more environmentally friendly, the starch acted to sequester the tellurium salt, thereby ensuring a homogeneous distribution of the desired phase throughout the composite precursor material.…”
Section: (D ) Starchmentioning
confidence: 99%